Sexually transmitted infections in indigenous communities of the Alto Rio Solimões - Gruber, André Gabriel; Pereira, Pablo Michel Barcelos; Goldim, Mariana Pereira de Souza; Cassol, Maria Eduarda Grasel; Portela, Williams Ferreira; Bitencourt, Rafael Mariano de (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: The prevalence of sexually transmitted infections (STI) among indigenous communities is an appalling issue related to Brazilian public health, as there is an increasing underreporting and neglect related to the study and care of these people. Objective: To determine the prevalence of STI in the indigenous population of the Alto Rio Solimões. Methods: STI diagnostic records from the database of the Indigenous Health Care Information System - SIASI, of the indigenous communities of the Alto Rio Solimões, belonging to the Nova Itália base, in Amazonas, were evaluated during the period from January 2010 to August 2020. Sociodemographic data were also evaluated to determine the profile of the diagnosed indigenous population and the geographical and temporal distribution of cases. Results: The overall prevalence rate of STIs was 3.91% (113 notifications of STI in the population of 2890 indigenous people). The largest number of diagnosed cases was in Nova Itália (60.17%). The ethnic group with the highest number of cases was Tikuna (92.03%). Among the STI studied, gonorrhea / chlamydia had the highest prevalence (68.14%), followed by Hepatitis B (13.27%) and Syphilis (10.61%). Most cases were found among women (71.7%), aged 30–34 years. Conclusion: A higher prevalence of STIs was observed in indigenous women, mainly from the Nova Itália town and the Tikuna ethnic group.